The Weihe Points in Homeopathy - Seiler, Hanspeter (Homœopathic Links, 2017)
The Weihe points are a useful additional tool in homeopathic diagnostics. The article contains a brief description of its physiological basis, provenience, and practical use.
Keywords: Weihe points; Physiological examination; Rademacher; Head's zones; Acupuncture points; Homeosiniatry; Causticum; Belladonna